2014
DOI: 10.1039/c3lc51061a
|View full text |Cite
|
Sign up to set email alerts
|

Durable spatiotemporal surveillance of Caenorhabditis elegans response to environmental cues

Abstract: Animal response to changes in environmental cues is a complex dynamical process that occurs at diverse molecular and cellular levels. To gain a quantitative understanding of such processes, it is desirable to observe many individuals, subjected to repeatable and well defined environmental cues over long time periods. Here we present WormSpa, a microfluidic system where worms are individually confined in optimized chambers. We show that worms in WormSpa are neither stressed nor starved, and in particular exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 33 publications
1
77
0
Order By: Relevance
“…28 Various microfluidic devices have been reported that trap multiple animals for high-throughput imaging, 29 automated sorting, 30 quantification of muscular forces, 31 chemosensory analyses, 25,32 electrotaxis, 33,34 thermosensory analyses, 35,36 and whole-animal stress responses. 24,37 A long term culture platform for C. elegans based on microfluidic approaches has also been presented. 24,27 Here, we introduce a device that facilitates streamlined and high-resolution imaging of the mechanosensory response in combination with mechanical stimulation in C. elegans .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Various microfluidic devices have been reported that trap multiple animals for high-throughput imaging, 29 automated sorting, 30 quantification of muscular forces, 31 chemosensory analyses, 25,32 electrotaxis, 33,34 thermosensory analyses, 35,36 and whole-animal stress responses. 24,37 A long term culture platform for C. elegans based on microfluidic approaches has also been presented. 24,27 Here, we introduce a device that facilitates streamlined and high-resolution imaging of the mechanosensory response in combination with mechanical stimulation in C. elegans .…”
Section: Introductionmentioning
confidence: 99%
“…24,37 A long term culture platform for C. elegans based on microfluidic approaches has also been presented. 24,27 Here, we introduce a device that facilitates streamlined and high-resolution imaging of the mechanosensory response in combination with mechanical stimulation in C. elegans . Importantly, physical access to the immobilized worm is necessary for applying mechanical stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…DAF-16, one of the members of the FOXO transcription factor that acts in dauer formation, longevity, fat metabolism, stress response, and innate immunity [42,43]. In live C. elegans under standard culture condition, the DAF-16 protein is broadly expressed both in the cytoplasm and nuclei.…”
Section: Stress Response To Different Concentration Of Bacteriamentioning
confidence: 99%
“…Although challenging in traditional culture systems, controllable spatiotemporal exposure to stimuli for long periods is possible with microfluidic devices. For instance, chips have been developed for life-long culture and imaging of C. elegans under a variety of conditions such as exposure to chemicals, immobilization for high-resolution imaging, and behavior tracking [51,52,[86][87][88][89]. These experiments, however, impose several difficulties.…”
Section: Control Of Flowmentioning
confidence: 99%